Shakespeare and Scotland - Maley, Willy; Murphy, Andrew (Andrew D.); Frost, Matthew; Manchester University Press (Manchester, UK : Manchester University Press, 2018)
Shakespeare and Scotland is a timely collection of new essays in which leading scholars on both sides of the Atlantic address a neglected national context for an exemplary body of dramatic work too often viewed within a narrow English milieu or against a broad British backdrop. These essays explore, from a variety of critical perspectives, the playwright's place in Scotland and the place of Scotland in his work. From critical reception to dramatic and cinematic adaptation, the contributors engage with the complexity of Shakespeare's Scotland and Scotland's Shakespeare. The influence of Scotland on Shakespeare's writing, and later on his reception, is set alongside the dramatic effects that Shakespeare's work had on the development of Scottish literature, from the Globe to globalisation, and from Captain Jamy and King James to radical productions at the Citizens' Theatre in Glasgow.
Acknowledgements -- Notes on contributors -- Introduction / Willy Maley and Andrew Murphy -- 1. "Stands Scotland where it did?" Shakespeare on the march / David Baker -- 2. Wrapped in the strong arms of the Union: Shakespeare and King James / Neil Rhodes -- 3. The place of Scots in the Scottish play: 'Macbeth' and the politics of language / Christopher Highley -- 4. 'Macbeth' and the rhetoric of political forms / Elizabeth Fowler -- 5. 'Hamlet's country matters: The 'Scottish play' within the play / Andrew Hadfield -- 6. How Scottish was the Scottish play? 'Macbeth's national identity in the eighteenth century / Rebecca Rogers -- 7. The Bard: Ossian, Burns, and the shaping of Shakespeare / Robert Crawford -- 8. "Not fit to tie his brogues": Shakespeare and Scott / Lidia Garbin -- 9. Shakespeare goes to Scotland: A brief history of Scottish editions / Andrew Murphy -- 10. Citz Scotland where it did?: Shakespeare in production at the Citizens' Theatre, Glasgow, 1970-1974 / Adrienne Scullion -- 11. Local 'Macbeth'/Global Shakespeare: Scotland's screen destiny / Mark Thornton Burnett.
In-house editor: Matthew Frost.
Includes bibliographical references and index.
Scholars and general readership of Shakespeare.
In English.
Print version record
JSTOR
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge; Shakespeare, William, -- 1564-1616 -- Influence; Shakespeare, William, -- 1564-1616 -- Appreciation -- Scotland; Shakespeare, William, -- 1564-1616; Shakespeare, William -- 1564-1616; Shakespeare, William; English literature -- Scottish authors -- History and criticism; Scottish literature -- History and criticism; National characteristics, Scottish, in literature; Scotland -- In literature; Scots in literature; Littérature anglaise -- Auteurs écossais -- Histoire et critique; Littérature écossaise -- Histoire et critique; Écossais dans la littérature.; Écosse -- Dans la littérature.; Literature and literary studies; Literary studies: general -- Literary studies: c. 1500 to c. 1800.; DRAMA -- Shakespeare; Scots in literature; Scottish literature; National characteristics, Scottish, in literature; Literature; Influence (Literary, artistic, etc.); English literature -- Scottish authors; Art appreciation; Scotland; Biography, Literature & Literary studies -- Plays, playscripts -- Classic & pre-20th century plays; Rezeption; Schottland; DRAMA / Shakespeare; Electronic books; Criticism, interpretation, etc